Rancangan Irigasi Sprinkler Portable Tanaman Pakchoy - Ahmad Tusi; Budianto Lanya (Balai Teknik Irigasi, 2016)
Sprinkler irrigation is one of the most efficient and effective effective irrigation. However, on-site application of sprinkler irrigation systems has encountered many obstacles, including the initial investment and operational costs. This study aimed to design a sprinkler irrigation system which saves the initial investment cost and simple in operation and maintenance, especially in the area where agricultural land were separated and small in area (0.10 to 0.30 ha) or without irrigation facilities. The research method in this study were the determination of the length and diameter of the pipe based on analysis of hydraulic pipe in lateral, manifolds and main pipe; sprinkler discharge calculation with volumetric method; and determination of irrigation uniformity with Christiansen method. The portable sprinkler irrigation system has specification: sprinkler nozzle head Impact Plactic type with nozzle size 4 mm, total height riser stick 1.3 meters in diameter ¾